CLONING OF THE BACTERIAL ESTERASE GENE AND DETERMINATION OF THE BIOCHEMICAL CHARACTERISTICS OF THE RECOMBINANT ENZYME - Mussakhmetov, A.; Astrakhanov , M.; Aktayeva , S.; Silayev , D.; Khassenov , B. (Eurasian Journal of Applied Biotechnology, 2025)
Esterases are hydrolytic enzymes that catalyze the hydrolysis and transesterification of short-chain fatty acid esters. They are widespread in nature and can be found in plants, animals, and microorganisms. Microbial esterases are used in the production of biofuels, and in cosmetic, food, and pharmaceutical industries. Recently, microbial esterases have attracted interest due to their ability to hydrolyze plastics, particularly polyethylene terephthalate (PET). It was established that Bacillus paralicheniformis T7 secretes an enzyme with esterase activity of 18.32 ± 2.38 U/mL. Protein mass spectrometry in combination with proteomic and genomic analysis identified a bacillary esterase with a molecular weight of 26.8 kDa. Based on the complete genome sequence of the strain, oligonucleotides were designed to amplify the esterase gene, which was subsequently cloned into the pET-28c(+) vector. Transformation of Escherichia coli BL-21(DE3) cells with the esterase-containing vector resulted in a strain that produced recombinant esterase with a yield of 614 mg/L. The recombinant esterase was purified using Ni-NTA affinity chromatography on a Ni²⁺ column. Studies revealed that the recombinant esterase exhibits maximum activity at 40 °C and pH 7.0. The enzyme remains active within the temperature range of 30–55 °C and pH 5.0–8.0. Thermostability assays demonstrated that the esterase is stable after 15 minutes of incubation at 30–50 °C and within the pH range of 8.0–10.0. Submerged fermentation of B. paralicheniformis T7 followed by drying of the culture supernatant yielded a preparation with esterase activity of 15,328.1 ± 528.6 U/g. The results indicate that B. paralicheniformis T7 is a promising esterase-producing strain, and the enzyme itself holds potential for use as a hydrolytic biocatalyst in the degradation of fatty acid esters.